Analisis Pemecahan Masalah Pendidikan Matematis Materi Bilangan Pada Kelas IV SD 4 Karangmalang - Dwi Aqiella Fadilla Hayya; Mareta Noor Ahadiya; Muhammad Erfansyah; Fitriyah Amaliyah (FKIP, Universitas Palangka Raya, 2024)
This study aims to analyze the ability to solve mathematical problems especially in the matter of numbers, as well as classify students' problem-solving abilities. In this study using a qualitative descriptive method. The population of this study were all fourthgrade students at SD 4 Karangmalang with a total sample of 9 students. This study collected data using observation, written tests, interviews and documentation. The written test consists of 5 essay questions in the form of word problems regarding mathematics in learning mathematics. In making written test questions, we use indicators of mathematical problem solving, namely: 1) Understanding new mathematical knowledge through problem solving, 2) designing mathematical models, 3) implementing and adapting appropriate strategies to solve problems, 4) completing models, 5) unifying and reflection of the process of solving mathematical problems. Of the 5 questions, they are then assessed with an assessment rubik according to the points specified in the question grid used. The results of the assessment were put into 3 categories, namely high category, medium category and low category in class IV SD 4 Karangmalang.